Boundary Element Modeling of Two‐Plate Interaction at Subduction Zones: Scaling Laws and Application to the Aleutian Subduction Zone. Issue 6 (11th June 2018) - Gerardi, G.; Ribe, N. M.
Abstract: This work uses the boundary element method (BEM) to explore the dynamics of subduction of a dense lithospheric plate (subducting plate, SP) beneath an overriding plate (OP). For simplicity, the model is two dimensional, the plates are purely viscous, and the ambient fluid is infinitely deep. The negative buoyancy of the slab is the only driving force of the system. First, we study the SP kinematics focusing on two characteristic instantaneous velocities: the convergence speed ( V Conv ) of the descending slab and the horizontal plate speed ( U SP ) of the flat portion of the SP. We find that V Conv is entirely controlled by the slab's geometry, by the width of the lubrication layer d 2 separating the SP and the OP, and by the SP's flexural stiffness St. Turning to U SP, we find that this parameter depends not only on d 2 and St but also on the lengths L SP and L OP of the two plates. The dependence of U SP on L SP is exactly logarithmic, both with and without an OP. Next, we explore the deformation of the OP, which occurs by a combination of extension/compression and bending. The OP deformation is compression dominated close to the trench and bending dominated along the remaining portion of the OP that undergoes significant deformation. For a positively buoyant OP, backarc extension is also observed. Finally, we estimate the subduction interface viscosity η SI of the central Aleutian subduction zone, running our BEM model with the appropriate geometry according to Lallemand et al. (2015, https://doi.org/10.1029/2005GC000917 ). We find η SI = (0.96–1.72) ×10 20 Pa s. Key Points: The subduction interface strongly affects the kinematics of the subducting plate; the plate speed depends logarithmically on the plate length Overriding plate deformation occurs by a combination of extension/compression and bending We estimate an interface viscosity (0.96–1.72) × 10 20 Pa s for the central Aleutian subduction zone